2013
DOI: 10.1186/1471-2261-13-96
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of subclinical carotid atherosclerosis and its relationship with echocardiographic parameters in non-diabetic chronic kidney disease patients

Abstract: BackgroundNon-diabetic chronic kidney disease (CKD) patients are a heterogeneous group with a variety of prognosis. We investigated the role of subclinical carotid atherosclerosis for the prediction of adverse cardiovascular (CV) outcomes in these patients, and tried to identify clinical and echocardiographic parameters associated with subclinical carotid atherosclerosis.MethodsAs a prospective design, 182 asymptomatic non-diabetic CKD patients underwent carotid ultrasonography and Doppler echocardiography. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In a longitudinal study of 3364 outpatients with and without CKD, lower creatinine clearance and higher cIMT were associated with fatal and nonfatal vascular events (74). However, in a study of nondiabetic outpatients with eGFR,60 ml/min per 1.73 m 2 , carotid plaque burden but not cIMT was associated with fatal or nonfatal acute coronary syndrome (ACS) or stroke (75). Similarly, Marcos et al did not show a significant association between the severity of cIMT and CV events or death (76).…”
Section: Cimt and Clinical Outcomesmentioning
confidence: 99%
“…In a longitudinal study of 3364 outpatients with and without CKD, lower creatinine clearance and higher cIMT were associated with fatal and nonfatal vascular events (74). However, in a study of nondiabetic outpatients with eGFR,60 ml/min per 1.73 m 2 , carotid plaque burden but not cIMT was associated with fatal or nonfatal acute coronary syndrome (ACS) or stroke (75). Similarly, Marcos et al did not show a significant association between the severity of cIMT and CV events or death (76).…”
Section: Cimt and Clinical Outcomesmentioning
confidence: 99%
“…In CKD patients, carotid intima media thickness (IMT) has been demonstrated to be increased as compared to healthy patients 7,8 and to be an independent predictor of all-cause and cardiovascular mortality 9 . In addition, carotid plaque largely increases the risk of CV events 10 . Recent results from the multicenter prospective observational NEFRONA study 11 , that includes CKD patients and controls without previous cardiovascular events, have shown that the prevalence of atheromatous plaques is higher among CKD patients, correlating with the severity of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular calcification, common carotid intima media thickness (CCA-IMT) and the presence of carotid plaques are strongly associated with cardiovascular disease in chronic kidney disease (CKD) patients [ 1 , 2 ]. Arterial thickening contributes to elevated risk of cardiovascular episodes in patients on maintenance renal replacement therapy.…”
Section: Introductionmentioning
confidence: 99%